MicroRNA Signature in Melanoma: Biomarkers and Therapeutic Targets - Ghafouri-Fard, Soudeh; Gholipour, Mahdi; Taheri, Mohammad (Frontiers in Oncology, 2021)
Melanoma is the utmost fatal kind of skin neoplasms. Molecular changes occurring during the pathogenic processes of initiation and progression of melanoma are diverse and include activating mutations in BRAF and NRAS genes, hyper-activation of PI3K/AKT pathway, inactivation of p53 and alterations in CDK4/CDKN2A axis. Moreover, several miRNAs have been identified to be implicated in the biology of melanoma through modulation of expression of genes being involved in these pathways. In the current review, we provide a summary of the bulk of information about the role of miRNAs in the pathobiology of melanoma, their possible application as biomarkers and their emerging role as therapeutic targets for this kind of skin cancer.